Transformasi Museum Hagia Sophia oleh Erdogan Persfektif Sejarah dan Implikasinya bagi Indonesia - Budi Sujati; Wahyu Iryana (Institut Agama Islam Negeri Padangsidimpuan, 2020)
The conquest of Constantinople in 1453 became the highlight of the world today one of the triggering of Turkish President Recep Tayyip Erdogan changed the status policy of the museum's Hagia Sophia to the mosque. It gets a tremendous response from the world community especially from the West and Islam. Pros and cons arise because they assess the status of Hagia Sophia is a world heritage that can not change its status and must be a cultural property. From the stronghold in favor of arguing that it is the right and freedom of a country to change its identity with the support of its people. While those who reject the status of the change are due to access to visit the most sacred and sacred places will have difficulties so it will be difficult to visit them freely. This research is descriptive with a qualitative methodology. It used this methodology to explain a phenomenon that is happening now regarding the issue of Hagia Sophia. As Muslims must make wise decisions by its history through historical approaches with heuristic stages, criticism, interpretation, and historiography.